The Effect of Human Resource Competencies, Accounting Information Systems, Internal Control Systems, Characteristics of SMEs on the Quality of Financial Reports - Nugroho, Prihasantyo Siswo; Ristianawati, Yuyun; Astuti, Ratna Puji (Journal of Economics and Public Health, 2025)
The purpose of this study was to determine the effect of human resource competencies , accounting information systems, internal control systems, and MSME characteristics on the quality of financial statements . The data in this study were collected by conducting a questionnaire survey on 100 MSME players in Pekalongan Regency) to analyze the role of human resource competency variables, accounting information systems , internal control systems , and MSME characteristics in improving the quality of financial reports . The data collection technique used a simple random sampling technique with the Slovin formula to obtain a sample of 100 MSME actors . The results of this study provides evidence that human resource competencies and accounting information systems have an influence on the quality of financial statements . Meanwhile , the internal control system and the characteristics of MSMEs have no influence on the quality of financial statements . So the influential variables in this study are human resource competencies and accounting information systems.